2017
DOI: 10.1016/j.urology.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Same-Session Bilateral Ureteroscopy: Safety and Outcomes

Abstract: Bilateral ureteroscopy can be performed safely with short-term complications, consistent with published literature. We found no long-term complications and high stone-free rates. Bilateral ureteroscopy in a single procedure represents a viable standard of care for patients with bilateral stone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…6,7,10 Previous retrospective series reported that SFR ranged from 42.0% to 92.8%. [11][12][13][14][15][16] This wide range reflects the different image modalities used to evaluate this outcome. Lack of a comparative group makes these low-quality data.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,10 Previous retrospective series reported that SFR ranged from 42.0% to 92.8%. [11][12][13][14][15][16] This wide range reflects the different image modalities used to evaluate this outcome. Lack of a comparative group makes these low-quality data.…”
Section: Discussionmentioning
confidence: 99%
“…Published complication rates from earlier cohort series of bilateral URS procedures ranged from 10% to 29% [9] , [10] , [11] , [12] , [13] , [14] , [15] . In the most recent study published on same-session URS, complication rates were reported to be 16.2% [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Ingimarsson et al [20] evaluated unilateral URS procedures from their own database with a complication rate of 15.8%. No significant difference between the same-session bilateral and single-session unilateral URS was found in terms of complications ( P = 0.79).…”
Section: Discussionmentioning
confidence: 99%
“…There were 16 studies [7][8][9][10][11] of bilateral simultaneous ureteroscopy (BS-URS), including 1073 patients (660 men, 413 women) with a mean age of 46.5 years. Stone proportions were reported in size or burden by different studies and are summarised in Table 1.…”
Section: Bilateral Simultaneous Ureteroscopy (Table 1)mentioning
confidence: 99%
“…This review provides an up to date and comprehensive overview on bilateral simultaneous endourological procedures for bilateral stone disease [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A total of 1966 patients (across 32 studies) were included.…”
Section: Meaning Of the Studymentioning
confidence: 99%